(untitled) (Bangladesh Journal of Zoology, 2012)
The present study was designed for the qualitative and quantitative detection of Giardia in the Pagla Sewage Treatment Plant (PSTP) in Dhaka. The physico-chemical parameters of the sewage water were also recorded. Total 72 raw and treated samples were collected from PSTP throughout the year 2008 and these were processed with the Formol-Ether Concentration method and IMS followed by microscopy to identify Giardia in the sewage water. The protozoan parasite Giardia was abundant (2.23±1.44 × 105 cyst/l) in the sewage water dominating the sampling sites-Grit chamber (44%), Measuring chamber (34%) and Outlet lagoon (38%). A low abundance of Giardia in the PSTP starting from the first point to the last one indicates the waste water treatment efficiency for removal of the pathogen. A significant correlation was found for log (number of Giardia +1) with turbidity (r= 0.729) and TDS (r= 0.536) at 0.01level. DOI: http://dx.doi.org/10.3329/bjz.v39i2.10578 Bangladesh J. Zool. 39(2): 147-156, 2011